The impact of social transfers on labor supply: a comparative analysis of Turkey and the EU - Doğan, Fadime İrem (My University, 2018)
Bireysel durumlara katkıda bulunmak ve sosyal refaha ulaşmak amacıyla, kamu kuruluşları tarafından belli bir sosyal seviyenin altındaki vatandaşlara sağlanan her türlü ürün ve servislere sosyal transferler adı verilir. Sosyal transferlerin birçoğu hane halklarına, iş gücü arzına önemli derecede etki eden iş gücüne katılma ya da yardım alma seçeneği sunar. Bu tez; Türkiye ve AB'de sosyal transferlerin iş gücü arzına olan etkisini incelemeyi amaçlamaktadır. Zaman içerisinde hem Türkiye'de hem de AB'de farklı türde sosyal transferler için birçok politika ve reformlar uygulanmıştır. Ampirik analizler, 2006 – 2009 ve 2011 – 2014 periyodlarını içeren, TÜİK ve Eurostat'tan alınan Gelir ve Yaşam Koşulları Anketi (GYKA) aylık panel veri seti ile gerçekleştirilmiştir. Hızlandırılmış başarısızlık süresi (AFT) modeli kullanılarak regresyon tahminleri yapılmıştır. Seçilen beş ülke için elde edilen bulgular, her iki dönemde de işsizlik yardımı ödeneklerinin işsizlik süresini uzattığı yönündedir. İlk dönemde, toplam sosyal transferlerle yapılan analizler Hollanda'da toplu sosyal transferlerin işsizlik süresini azalttığını ama diğer ülkelerde uzattığını göstermektedir. Bunun yanında, ikinci periyodu içeren analiz sonuçların bulguları, toplu sosyal transferlerin (eğitim, maluliyet, yaşlılık ve ölüm, vb.) işsizlik süresini artırdığını ifade etmektedir. Tezin bulguları, iş arama teorisinin bir doğrulaması niteliğinde değerlendirilebilir. Bununla birlikte, sosyal transfer kaynaklarının verimsiz dağıldığı ve eğitim önemli alanlarda verimsiz yatırımların yapıldığı sonucundadır. Özellikle yaşlı çalışanlar için yatırımların kurslara ağırlık verilerek yeniden dağıtılması gerektiği çıkarılabilecek ilk politika önerileri arasındadır.

Social transfers define all forms of goods and services provided by the public authority to their citizens, who are below a certain social level, with the aim of contributing to individual conditions and further to social welfare. Most of the social transfers are under the category of giving an option to the households to choose between providing labor or receiving allowance, which can have significant impacts on labor supply. This dissertation attempts to investigate the impact of the social transfers on labor supply in Turkey and the EU. Through time, various policies and reforms have been conducted both in Turkey and EU member states regarding the different types of social transfers. It can be assumed that all social transfers have effect on labor supply. Panel of Income and Living Conditions Survey (SILC and EU-SILC) data is taken from TurkStat and Eurostat to conduct the empirical analyses of monthly periods over 20062009 and 2011-2014. The estimation is conducted by applying Accelerated Failure Time (AFT) model. The empirical results demonstrate that in all five countries receiving unemployment benefits prolongs unemployment duration in both periods. In 2006 – 2009 period, social transfers, as a total is significant with negative sign saying that the more individuals receive social transfers, the shorter their unemployment duration in the Netherlands. Whereas, results of the rest of the countries indicate that social transfers as a whole prolong the unemployment spell. The findings regarding total social transfers show that probability of leaving unemployment is longer for the ones who receive variety of transfers (education, disability, old age, survivors, etc.) for all countries in 2011 – 2014 period. The findings may be validation for the job search theory and signaling for inefficient allocation of social transfer resources and suboptimal investment in areas like education. Especially, reallocation of investment in training toward old aged individuals may be the primary policy implication to be drawn.
Keywords: Accelerated Failure Time Model; Avrupa Birliği; Economic policy; Ekonomi politikası; European Union countries; Hızlandırılmış Başarısızlık Süresi Modeli Social Transfers; İnsan gücü politikası; İşgücü arzı; İşsizlik; İşsizlik Süresi; Labor supply; Manpower policy; Sağkalım Analizi; Sosyal Transferler; Survival Analysis; Unemployment; Unemployment Duration